A comprehensive approach to pain management for patients with degenerative joint disease - Protsenko, Galyna; Kateryna, Ivanova (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2024)
Osteoarthritis is a chronic degenerative-inflammatory joint disease, which is characterized by cartilage damage, bone epiphyses remodeling, osteophyte appearence, and persistent joint deformity. OA impairs the synthesis of proteoglycans by chondrocytes, increases the activity of proinflammatory cytokines (interleukin-1β, -4, -6, -17, -18, tumor necrosis factor-α), immunological changes occur by increasing the function of T-helper cells and the appearance of autoantibodies to cartilage components, activation of lipid peroxidation and reduction of antioxidant protection system. Osteoarthritis treatment is aimed to reducing pain, inflammation and slowing the degenerative changes in cartilage. Non-steroidal anti-inflammatory drugs (NSAIDs) to which Nabumeton («Synmethon») refers are prescribed as symptomatic drugs. It is a moderately specific inhibitor of COX-2, a characteristic feature of which is the lack of effect on the gastric mucosa due to its weak alkaline properties. It does not alter the pharmacokinetics of antacids, and conversely, aluminum-containing antacids do not have a significant effect on the bioavailability of naumetone. It differs from other acidic NSAIDs. The drug is recommended for long-term use in patients with Osteoarthritis with synovitis. Chondroprotectors, which modify the structure of cartilage, are assigned in parallel. Among them, the highest level of evidence is glucosamine sulfate and chondroitin sulfate. Chondroitin is a gel-forming polysaccharide with high hydrophilicity. Its hydrocolloid properties are responsible for protecting the cartilage during the loads. Glucosamine is a building material for glucosaminoglycans that form the cartilage structure. Combination medicines are increasingly being used for initial treatment — the «Protecon Fast®» NSAID with chondroprotectants and the «Protekon®» (glucosamine sulfate, chondroitin sulfate) by «Organosin Limited», manufactured by «Evertogen Life Sciences Limited». Taking one drug instead of several improves patient compliance and is pharmacologically sound.